Comparative study of source–drain contact metals for amorphous InGaZnO thin‐film transistors. Issue 6 (16th December 2014) - Nag, Manoj; Bhoolokam, Ajay; Steudel, Soeren; Chasin, Adrian; Groeseneken, Guido; Heremans, Paul
Abstract In this work, we compared the thin‐film transistor (TFT) characteristics of amorphous InGaZnO TFTs with six different source–drain (S/D) metals (MoCr, TiW, Ni, Mo, Al, and Ti/Au) fabricated in bottom‐gate bottom‐contact (BGBC) and bottom‐gate top‐contact (BGTC) configurations. In the BGTC configuration, nearly every metal can be injected nicely into the a‐IGZO leading to nice TFT characteristics; however, in the BGBC configuration, only Ti/Au is injected nicely and shows comparable TFT characteristics. We attribute this to the metal‐containing deposits in the channel and the contact oxidation during a‐IGZO layer sputtering in the presence of S/D metal. In bias‐stress stability, TFTs with Ti/Au S/D metal showed good results in both configurations; however, in the BGTC configuration, not all the TFTs showed as good bias results as Ti/Au S/D metal TFTs. We attribute this to backchannel interface change, which happened because of the metal‐containing deposits at the backchannel during the final the SiO2 passivation.